Correlation Between Reading Literacy Ability and Achievement in Learning Indonesian Language in Grade X - Muakibatul Hasanah; Risa Yanuarti Sholihah (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
This study aims to find out (1)  reading literacy ability, (2)  achievement in Indonesian language learning, and (3) correlation between reading literacy ability and achievement in Indonesian language learning in Grade X. This research uses a quantitative approach of a correlational research type. The results of this study indicate that (1) the score rate of reading literacy ability of  students is 78.3 (good), (2) the score rate of achievement in Indonesian language learning  is 81,7 (good), and (3) there is a significant correlation between reading literacy ability and achievement in learning Indonesian language in Grade X.